Costs of cancer along the care continuum: What we can expect based on recent literature. Issue 21 (17th October 2018) - Pisu, Maria; Henrikson, Nora B.; Banegas, Matthew P.; Yabroff, K. Robin
Abstract : Background: Cancer costs should be discussed by patients and providers, but information is not readily available. Results from recently published studies (in the last 5 years) on direct and indirect cancer costs may help guide these discussions. Methods: The authors reviewed studies published between 2013 and 2017 that reported direct health care costs and indirect (productivity losses) costs. The annual mean total and net costs of cancer were summarized for all payers and for survivors only by age (ages 18‐64 and ≥65 years), by phase of care (initial [ie, 12 months from diagnosis], continuing, and end‐of‐life [ie, 12 months before death]), or for recently diagnosed (within 1‐2 years of diagnosis) and longer term survivors. Results: For all payers combined, costs for cancers like breast, prostate, colorectal, and lung cancers were 20, 000 to 100, 000 in the initial phase, 1000 to 30, 000 annually in the continuing phase, and ≥60, 000 in the end‐of‐life phase. Annual out‐of‐pocket costs to recently diagnosed survivors were >1000 for medical care and time costs, approximately 2000 for productivity losses, and from 2500 to >4000 for employment disability, depending on age. For longer term survivors, the cost of medical care was approximately 1500 for older survivors and 747 for younger survivors, time costs were 831 to 955 for older survivors and 459 to 630 for younger survivors, and productivity losses were approximately 800. Disability among long‐term survivors was similar to that among short‐term survivors. Limitations of the reviewed studies included older data and under‐representation of higher cost cancers. Conclusions: Frequently updated cost information for all cancer types is needed to guide discussions of anticipated short‐term and long‐term cancer‐related costs with survivors. Cancer 2018;000:000‐000 . © 2018 American Cancer Society . Abstract : This review of recently published studies provides perspective on the magnitude of total and out‐of‐pocket cancer costs along the care continuum. Information may be useful for providers to discuss costs with patients; however, limitations, such as the use of data that are older and that under‐represent poor‐prognosis, higher cost cancers, should be considered.